Vitamin D supplementation in patients with nonalcoholic fatty liver disease: A randomized controlled trial - Sakpal, Mallikarjun (JGH Open, 2017)
BACKGROUND AND AIM: Deficiency of vitamin D may be related to the pathogenesis of nonalcoholic fatty liver disease (NAFLD). The aim of the present study was to evaluate the effect of vitamin D supplementation in patients with NAFLD. METHODS: A total of 81 patients with NAFLD with normal or raised (n = 47) serum alanine aminotransferase (ALT) having vitamin D deficiency were randomized prospectively. Group 1 (n = 51) received lifestyle modifications and a single injection of vitamin D (600 000 U) (standard medical treatment [SMT] + vitamin D) and group 2 (n = 30) received lifestyle modifications (SMT) for 6 months. The primary objective of this study was to assess the improvement in insulin resistance (IR) and serum ALT (in patients with raised ALT) and the secondary objective was to assess the change in cytokine profile in the SMT + vitamin D group. RESULTS: After 6 months, significant improvement in serum levels of ALT was observed in the SMT + vitamin D group when compared to the SMT group (ALT [87 ± 48 and 59 ± 32 IU/mL, P < 0.001] vs [64 ± 35 and 62 ± 24 IU/mL, P = 0.70]). Mean insulin levels and homeostasis model assessment‐IR remained unchanged at 6 months in the SMT + vitamin D group while there was a significant increase in mean insulin and homeostasis model assessment‐IR in the SMT group. SMT + vitamin D group had significant increase in mean serum levels of adiponectin (836 ± 309 and 908 ± 312 (pg/mL), P = 0.018) compared with the baseline; tumor necrosis factor‐α levels decreased from baseline but the change was not significant. CONCLUSION: Patients with NAFLD given vitamin D in addition to lifestyle modifications have significant improvement in serum ALT and serum adiponectin levels.